2021
DOI: 10.1007/s12094-021-02665-y
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative radiotherapy after upfront radical prostatectomy: debated issues at a turning point—a survey exploring management trends on behalf of AIRO (Italian Association of Radiotherapy and Clinical Oncology)

Abstract: Objectives Postoperative prostate cancer patients are a heterogeneous population, and many prognostic factors (e.g., local staging, PSA kinetics, margin status, histopathological features) may influence their clinical management. In this complex scenario, univocal recommendations are often lacking. For these reasons, the present survey was developed by the Italian Association of Radiotherapy and Clinical Oncology (AIRO) to collect the opinion of Italian radiation oncologists and delineate a representation of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Alternatively, PSA can be followed over time, and only when it begins to present values >0.2 ng/mL in two consecutive dosages, a salvage RT can be done. 16 Some studies have shown that salvage radiotherapy is not inferior to adjuvant radiotherapy in terms of oncological outcomes, and moreover it would seem to ensure lower toxicity. 6 Currently, urinary toxicity remains one of the main clinical issue in this scenario, being the bladder neck part of the treatment volume.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, PSA can be followed over time, and only when it begins to present values >0.2 ng/mL in two consecutive dosages, a salvage RT can be done. 16 Some studies have shown that salvage radiotherapy is not inferior to adjuvant radiotherapy in terms of oncological outcomes, and moreover it would seem to ensure lower toxicity. 6 Currently, urinary toxicity remains one of the main clinical issue in this scenario, being the bladder neck part of the treatment volume.…”
Section: Discussionmentioning
confidence: 99%